Health insurance demand among formal sector employees in Addis Ababa, Ethiopia - Obse, Amarech Guda (Trinity College (Dublin, Ireland). Department of Public Health and Primary Care, 2014)
Understanding and predicting consumer preferences for alternative health insurance design packages is important for a country striving to introduce health insurance. Historically health services and health insurance programmes were decided by medical professionals. Though, a considerable amount of research has been conducted in preference elicitation in health care, there are only a handful of studies in the area of health insurance. Analysis of the preference for health insurance is vital as it provides information to help the efficient allocation of resources. Particularly, introducing a new health insurance system requires a good understanding of both the demand and supply side factors which are crucial for an effective health insurance intervention.
Keywords: Global Health, Ph.D.; Ph.D. Trinity College Dublin